Incidence and risk factors for unplanned readmission after total hip arthroplasty for osteonecrosis of the femoral head - Wang, Meng; Yang, Xuemei; Li, Junyong; Li, Chengsi; Zhang, Yulong; Hao, Xuewei (Frontiers in Surgery, 2024)
ObjectiveTo investigate the incidence, primary causes, and risk factors for unplanned readmissions within one year after the first primary total hip arthroplasty (THA) for osteonecrosis of the femoral head (ONFH).MethodsData were retrospectively collected from patients who had undergone the first primary THA for ONFH at two tertiary hospitals between January 2021 and December 2022, with complete 1-year follow-up assessments. Patients who experienced an unplanned readmission within 1 year were classified as the readmission group, while the others as the non-readmission group. The incidence rate and primary causes of unplanned readmission were determined, and the risk factors were identified through univariate and multivariate analyses.ResultsA total of 594 eligible patients were included, with 363 being men (61.1%) and an average age of 59.2 years at the time of surgery. Forty-seven patients were readmitted within one year, representing an accumulated rate of 7.9%. Among these, 18 (38.3%) readmissions occurred within 30 days and 27 (57.4%) within 90 days. The primary reasons for readmissions included hip dislocation (35.3%), followed by periprosthetic fracture, deep vein thrombosis, delayed incision healing, surgical site infection and others. The multivariate regression model revealed that age (every 10-year increment, OR, 1.39; 95% CI, 1.12–1.88), ARCO stage IV vs. Ⅲ (OR, 3.72; 95% CI, 1.96–7.22), CCI ≥4 vs. <4 (OR = 5.49; 95% CI, 2.16–13.77), admission anemia (OR, 2.72; 95% CI, 1.37–6.83) and surgeon inexperience (OR, 2.74; 95% CI, 1.29–6.73) were significantly associated with unplanned readmission.ConclusionsThese findings provide valuable clinical insights into unplanned readmission after THA for ONFH and may aid in preoperative counselling for patients and enhance perioperative care.